"Negative Ties, Lost Ties, Latent Ties". Issue 121 (January 2014) - Chauvac, Nathalie; Cloutier, Laurence; Defossez, Adrien; Akermann, Grégori; Federico, Ainhoa de
This special issue intends to bring a unique perspective on some unexplored aspects of social networks, namely the negative ties, lost ties or latent ties. The texts presented here were prepared following after a conference organized specifically on this topic. Field analyzes reflect the presence of social networks that are "inefficient", "conflictual", "absent" or "prohibited", and theoretical development has begun to explore and characterize these social ties. The emphasis here is on the methods used to understand these relatively difficult-to-grasp ties, both in theory and in practice. Taking into account such links, this work opens a heuristic path in social network analysis.